SITUATIONAL EFFICIENCY ANALYSIS OF THE TEAMS THAT PARTICIPATED IN 2008 EUROPEAN FOOTBALL CHAMPIONSHIP - Alen Kapidžić,; Ervin Bećirović,; Jasmin Imamović, (Sport Scientific And Practical Aspects, 2025)
We analyzed all European championship 2006 soccer games with basic aim to emphasize significant factors that have influence on success of soccer game. For examination we prepare following variables: ŠNGU16M – shots on goal in Penalty Area, ŠNGV16M – shots on goal outside Penalty Area, ŠPGU16M – shots wide in Penalty Area, ŠPGV16M – shots wide outside Penalty Area, BŠU16M – shots blocked in Penalty Area, BŠV16M – shots blocked outside Penalty Area, UPRPAS – Total passes completion, DUGPAS – Long passes, PRDUGPAS – Long passes completion, SREPAS – Medium passes, PRSREPAS – Medium passes completion, KRAPAS – Short passes, PRKRAPAS – Short passes completion. Criterion variable will be define by the number of shots that accomplish every team during the game. For determination variable, which have significant influence on success in soccer game, will be apply regression analysis.